Pro-Ecological Patterns of Behaviour of Polish Consumers on the Market of Ecological Products - A Research Concept - Jolanta TARAPATA; Alicja Katarzyna Krzepicka (Communications of International Proceedings, 2021)
Currents in consumption indicate that consumers of the 21st century are more and more demanding people, demanding that the products available on the market are diverse, of high quality with high nutritional value, manufactured using traditional methods or ensuring health safety. The analysis of the literature, observations and experiences of existing consumers as well as the analysis of the results of research on pro-ecological consumer behaviour indicate the need for constant identification and verification of consumer behaviour due to the growing ecological awareness of consumers, as well as the increasing number of organic products, the emergence of new product offers, or the possibility of shopping in specialised organic shops and at dedicated eco-shelves in supermarkets. The main objective of the planned research will be to determine the level of ecological awareness and attitudes of Polish consumers towards organic products and to assess their impact on their purchasing behaviour. The authors intend to monitor the behaviour and purchasing decisions of consumers regarding ecological products, their motivation, sources of information about ecological products, promotions used in specialised ecological shops, on separate eco-sites in supermarkets, verifying the determinants which, in the opinion of the respondents, can contribute to increasing their awareness, social responsibility and, consequently, to the development of eco-consumption. One of the results of the research will be the development of a typology of contemporary consumers, with a particular focus on defining the profile of the eco-consumer.
Keywords: Consumer Behaviour; Environmental Awareness; Greening Of Consumption.